New species Victoriopisa bruneiensis and Apocorophium acutum (Chevreux, 1908) from Brunei (Crustacea: Peracarida: Amphipoda) - Hossain, M. Belal; Hughes, L.e. (Zootaxa, 2016)
One new and one invasive species of amphipod are described from the subtidal waters of Brunei. The new species Victoriopisa bruneiensis (Melitidae) and the invasive species Apocorophium acutum (Chevereux, 1908) (Corophiidae) were collected from the Sungai Brunei Estuary. Victoriopisa bruneiensis sp. nov. is one of only four Victoriopisa where the eyes are present. An updated key to twelve world species of Victoriopisa is provided. Apocorophium acutum occurs in high density algal matts on pylons/rocks. This is the sixth species of Apocorophium described for the genus.